Uncertainty and the market for patents - Irene Troy; Raymund Werle (Max Planck Institute for the Study of Societies, 2008)
Modern societies regard knowledge as a production factor in its own right. The market is the prevailing governance mode of their economies, and it is supposed to be the most appropriate mode of trading and allocating knowledge assets, too. But socio-economic research has revealed that knowledge markets are far from functioning smoothly. Building on ongoing qualitative research into patent trading we suggest that the emergence of a well-functioning market for patented new technological knowledge is confronted with several obstacles, which can be characterized as different facets of uncertainty. They are included in the process of creation of innovative knowledge, in its transformation into a fictitious knowledge commodity (patent), in its uniqueness, in the strategy of transaction partners, in the estimation of the future market potential of final products (based on the patent), and generally in the problem of incomplete and asymmetric information. Also a commonly accepted method of determining a patent's value is missing. We analyze structural and organizational responses to the problem of uncertainty. Potential traders often rely on contractual options, especially licensing agreements, and complementary procedural principles facilitating the trade of patents. – – Moderne Gesellschaften betrachten Wissen als einen eigenständigen Produktionsfaktor. Die Wirtschaft dieser Gesellschaften koordiniert sich in zunehmendem Maße durch den Markt, der als angemessener Modus der Allokation von und des Handels mit Wissen angesehen wird. Einschlägige sozioökonomische Studien zeigen allerdings, dass von einem Markttausch höchstens eingeschränkt die Rede sein kann. Auf der Basis einer laufenden qualitativen Untersuchung zum Patenthandel identifizieren wir unterschiedliche Facetten umfassender Unsicherheit, mit denen die Akteure in diesem Feld konfrontiert sind. Die Quellen der Unsicherheit liegen im Prozess der Entwicklung innovativen Wissens und dessen Transformation in eine fiktive Ware (Patent) ebenso wie in der Einzigartigkeit des patentierten Wissens. Aber auch die Schwierigkeiten, das Marktpotenzial eines auf dem Patent basierenden Endprodukts einzuschätzen, die Strategien der Transaktionspartner und generell die Probleme unvollständiger und asymmetrischer Information verursachen Unsicherheit. Zudem gibt es keine allgemein akzeptierte Methode, den Wert eines Patents zu bestimmen. Wir analysieren strukturelle, organisatorische und prozedurale Reaktionen auf das Problem der Unsicherheit und zeigen, dass potenzielle Handelspartner auf vertragliche Vereinbarungen, insbesondere Lizenzverträge setzen, um Patente zu handeln.
Keywords: 300; Patent; Risiko; Markt; Lizenzvergabe